2022
DOI: 10.20343/teachlearninqu.10.36
|View full text |Cite
|
Sign up to set email alerts
|

Instructor Perception of Incorporating Active Learning in College of Agriculture Classrooms

Abstract: Significant numbers of studies declare the effectiveness of “active learning” and numerous universities develop programs to support the incorporation of active learning methods, yet despite various incentives, adoption is met with resistance. This work shares the results of a study of instructor perceptions about active learning at a large research university in the United States. Instructor motivation, perceptions of competence and autonomy (related to colleagues and administrators), experience in training pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Even though faculty of this study participated in a FDP, it cannot be assumed that they all engaged in AL with the same degree of depth, consistency, and assuredness. Research has identified a host of factors and perceived barriers to active learning, such as teaching competence, confidence, degree of comfort with learner-centered practices, and preoccupation with student evaluations (particularly for pre-tenured faculty), to mention a few (Karcher, et al 2022). Therefore, it is likely that students experienced a range of depth and quality of active learning methods in their courses of faculty that participated in FDP.…”
Section: Discussionmentioning
confidence: 99%
“…Even though faculty of this study participated in a FDP, it cannot be assumed that they all engaged in AL with the same degree of depth, consistency, and assuredness. Research has identified a host of factors and perceived barriers to active learning, such as teaching competence, confidence, degree of comfort with learner-centered practices, and preoccupation with student evaluations (particularly for pre-tenured faculty), to mention a few (Karcher, et al 2022). Therefore, it is likely that students experienced a range of depth and quality of active learning methods in their courses of faculty that participated in FDP.…”
Section: Discussionmentioning
confidence: 99%
“…Interest with a variety of processes and learning resources both inside and outside the classroom can bring knowledge and experiences to improve the quality of life of oneself, society, and the public (Ministry of Education 2018: [11][12][13][14]. Active learning is a process in which learners must take action (Bonwell & Jame, 1993; Holec & Marynowski, 2020; Karcher et al, 2022).…”
Section: Introductionmentioning
confidence: 99%